2019
DOI: 10.31219/osf.io/crzku
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of management systems on the performance of dromedary camel calves reared under organized farm condition

Abstract: Camel calves (10),7-to 10-month-old, were allotted randon1ly into 2 conlparable groups of 5 each. First group "vas reared under intensive systenl of management (ISM) with concentrate supplernentation. The second group was reared under semi-intensive system of nlanagement (8ISM) and allowed daily grazing/browsing for about 6 to 7 h. All animals were offered moth crop residue as manger feeding. Watering was done once daily for all camels in both the groups. After 180 days of trial period, Inean body weight and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 1 publication
4
9
1
Order By: Relevance
“…Bakheit et al (2012) reported significant differences in the mean daily weight gain (grams) under semi-intensive (535+9.83) and traditional management systems (TMS) (317+5.46), respectively. Feed intake: These findings are in line with the findings of Bhakat et al (2008) who studied the effect of management systems on growth performance of Indian camel calves and reported that the crop residue intake was significantly varied between two groups, 5.53 vs. 4.37 kg/calf/d in IMS and SIMS, respectively. Moreover, Saini et al (2014) reported higher DMI (kg/d) in stall fed pre-pubescent camels as compared to grazing group.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Bakheit et al (2012) reported significant differences in the mean daily weight gain (grams) under semi-intensive (535+9.83) and traditional management systems (TMS) (317+5.46), respectively. Feed intake: These findings are in line with the findings of Bhakat et al (2008) who studied the effect of management systems on growth performance of Indian camel calves and reported that the crop residue intake was significantly varied between two groups, 5.53 vs. 4.37 kg/calf/d in IMS and SIMS, respectively. Moreover, Saini et al (2014) reported higher DMI (kg/d) in stall fed pre-pubescent camels as compared to grazing group.…”
Section: Discussionsupporting
confidence: 87%
“…Growth rate: The average growth rate was significantly higher (P<0.05) in calves of IMS as compared to the calves of SIMS. These findings are in line with the findings of Bhakat et al (2008) who studied the effect of management systems on growth performance of dromedary camel calves in India, they used 10 camel calves aged between 7-10 months old in their study and divided them randomly into two comparable groups of 5 each. The average initial body weight of both groups was almost similar.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations